FEATURES OF THE CLINICAL COURSE OF HERPETIC INFECTION IN HIV-INFECTED PATIENTS - Valieva N.M. (Western European Studies, 2024)
Herpes infection in HIV-infected people is prone to recurrence; the more pronounced the immunodeficiency, the more persistent the infection, the higher the risk of developing generalized lesions. Purpose of the study: to study the clinical features of the course of herpetic infection in HIVinfected patients. Study materials: we conducted a prospective study analysis of 50 patients with HIV infection. The study group included HIV-infected patients at different stages of the disease aged from 18 to 40 years. Stage I - 12, stage II - 19, stage III - 16, stage IV - 3 patients. Results of the study: in all cases of the study, various forms of chronic herpetic infection were diagnosed, reactivation of which occurred in 38%, and a recurrent course in 62% of cases. Conclusions: the course of HI depends on the stage of HIV infection. The clinical picture of herpes infection in patients in stages III and IV of HIV infection is polymorphic and is manifested by lesions of internal organs.
Keywords: HIV infection; herpes infection; genital herpes; immunodeficiency